A superfamily of ıt Arabidopsis thaliana retrotransposons - Konieczny, A.; Voytas, D. F.; Michael P. Cummings; Ausubel, F. M. (GeneticsGenetics, 1991)
We describe a superfamily of Arabidopsis thaliana retrotransposable elements that consists of at least ten related families designated Ta1-Ta10. The Ta1 family has been described previously. Two genomic clones representing the Ta2 and Ta3 elements were isolated from an A. thaliana (race Landsberg erecta) lambda library using sequences derived from the reverse transcriptase region of Ta1 as hybridization probes. Nucleotide sequence analysis showed that the Ta1, Ta2 and Ta3 families share greater than 75% amino acid identity in pairwise comparisons of their reverse transcriptase and RNase H genes. In addition to Ta1, Ta2 and Ta3, we identified seven other related retrotransposon families in Landsberg erecta, Ta4-Ta10, using degenerate primers and the polymerase chain reaction to amplify a highly conserved region of retrotransposon-encoded reverse transcriptase. One to two copies of elements Ta2-Ta10 are present in the genomes of the A. thaliana races Landsberg erecta and Columbia indicating that the superfamily comprises at least 0.1% of the A. thaliana genome. The nucleotide sequences of the reverse transcriptase regions of the ten element families place them in the category of copia-like retrotransposons and phylogenetic analysis of the amino acid sequences suggests that horizontal transfer may have played a role in their evolution.